The histopathologic evaluation of local effects of ozone therapy on the healing of experimental calvarial defects of rats - Tolga Bayar; Ebru Deniz Karslı (BMC Oral Health)
Abstract Background This study evaluates the effects of ozone on hard and soft tissue healing when a free tissue flap is used to close wound areas lacking primary closure over autogenous grafted sites. Methods In our study, 24 male Wistar rats were divided into four groups: two control groups and two ozone-treated groups. All rats underwent the same surgical procedure. After surgery, the control groups received no additional treatment, while the ozone groups received topical ozone application. Ozone was applied for 2 min, three times per week, with one-day intervals, for a duration of 2 weeks post-surgery. Sacrifice was performed on the 14th day for one control and one ozone group, and on the 28th day for the remaining groups. All soft and hard tissue samples were then examined histopathologically. Clinical trial number: not applicable. Results Histopathological evaluations and statistical analyses on the 14th day indicated that bone healing was significantly better in the ozone group compared to the control group (p = 0.049). For soft tissue healing, although there was no statistically significant difference between the ozone and control groups, proportional values showed better recovery in the ozone-treated groups compared to the controls. Conclusions The present study concludes that ozone has a positive effect on new bone formation in the early stages; however, it showed no statistically significant effect on soft tissue healing. We believe that further comprehensive studies would be beneficial to confirm these findings.